Pengaruh “Konseling Menopause” Terhadap Sikap dan Kualitas Hidup Wanita Perimenopause Di Kecamatan Sukawati Bali - Ariani, Ni Komang Sri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
The number of postmenopausal women in Indonesia in 2018 as many as 22 million people, even predicted in 2025 there will be 60 million women who are going through menopause. The high number of the result of the higher life expectancy. At menopause women will have complaints, namely physical and psychological complaints. Every complaint experienced by menopausal women, can lead to decreased quality of life. Quality of life of postmenopausal women decreased, caused by menopausal women are not ready to accept the menopause. Women's attitudes toward menopause is one of the most significant factors affecting the experience of menopause. Women who are positive about the menopause will not have complaints that are too heavy. Efforts to prevent the quality of life of menopausal women decline is to provide counseling menopause. This type of research is a Quasi Experiment study design with one group pre test and post test design. The sampling stratified random sampling with a sample size of 35 people. The instrument used was a questionnaire Mames (Multi-dimensional Menopause Attitudes Scale) to measure attitudes and perimenopausal women WHOQOOL-BREF questionnaire (The World Health Organization Quality of Life) to measure the quality of life for perimenopausal women. Statistical testing using a paired t-test and Wilcoxon non-parametric analysis. The results showed "menopause counseling" can improve the attitude of perimenopausal women at 11,4% (p